Drinking water quality from rural handpump-boreholes in Africa. (27th May 2020) - Lapworth, D J; MacDonald, A M; Kebede, S; Owor, M; Chavula, G; Fallas, H; Wilson, P; Ward, J S T; Lark, M; Okullo, J; Mwathunga, E; Banda, S; et al.
Abstract: Groundwater provides a vital source of drinking water for rural communities in many parts of Africa, particularly in the dry season when there are few safe alternative sources. This paper summarises results from a study (n = 428) assessing dry season water quality, both microbiological and inorganic chemistry, in handpump equipped boreholes (HPBs) across the Ethiopia Highlands (n = 142), Malawi (n = 162) and Uganda (n = 124) using a stratified, randomised sampling design. This study seeks to examine general water quality by randomly sampling rural groundwater supplies across larger areas with different geology and climate. The majority, 72%, of HPBs surveyed provide good quality dry season drinking water as defined by WHO drinking water quality criteria. Within this overall picture, the most notable constraints were from thermotolerant coliforms (TTCs), which exceeded the WHO drinking water guideline of zero colony forming units (cfu/100 ml) in 21% of sites (range 0–626 cfu/100 ml). TTC contamination was found to have a significant and positive correlation with annual average rainfall (ρ = 0.2, p = 0.00003). Across all three countries, WHO health based chemical drinking water quality values were exceeded at 9% of sites and were found for manganese (4%), fluoride (2.6%) and nitrate (2.5%); arsenic concentrations were below the guideline value of 10 μ g l −1 (range < 0.5–7 μ g l −1 ). The high percentage of Mn exceedances (14% ± 5.2% >400 μ g l −1 ) found in drinking water sources in Uganda challenges the decision by WHO not to formalise a health-based guideline for Mn. While the overall level of microbiological contamination from HPBs is low, results from this study strongly suggest that at a national and regional level, microbiological contamination rather than chemical contamination will provide a greater barrier to achieving targets set for improved drinking water quality under the UN-SDG 6. Efforts should be made to ensure that boreholes are properly sited and constructed effectively to reduce pathogen contamination.